Потенціал використання понять «спосіб життя» та «стиль життя» для соціологічного аналізу практик щодо індивідуального здоров’я - Михайльова, Катерина; Mykhaylyova, Kateryna; Шкурапет, Наталія; Shkurapet, Nataliya (My University, 2020)
У статті розглянуто теоретичні основи досліджень феноменів способу життя та стилю життя. Здійснено ретроспективний аналіз підходів до їх трактування. Показано, що основними маркерами способу життя є види життєдіяльності й способи їх реалізації, що нормуються соціально-політичними, культурними або соціально-економічними конструкціями в суспільстві. Продемонстровано, що спосіб життя відбиває соціально типові практики. Стиль життя є більш індивідуалізованим феноменом, який має особливі прояви в повсякденному житті та вбудовується в соціальний простір кожним індивідом або групою. На основі різноманітних визначень цих понять здійснено їх порівняння. Розглянуто можливості використання зазначених категорій для аналізу феномену індивідуального здоров’я. На основі врахування його особливостей зроблено висновок про превалювання застосування поняття «здоровий спосіб життя» над терміном «здоровий стиль життя». Підкреслено, що їх розмежування може здійснюватися залежно від концепції дослідження з урахуванням континуумів «норма–варіативність», «соціальне–індивідуальне».

The theoretical bases of the analysis of the phenomena «way of living» and «lifestyle» are considered in the article. The retrospective analysis of approaches to its consideration is made. It is shown that the main markers of way of living are the types of life activity and ways of its implementation, which are normalized by socio-political, cultural or socio-economic structures in society. It has been demonstrated that way of living reflects socially typical practices. Lifestyle is a more individualized phenomenon that has particular manifestations in everyday life and is embedded in the social space by each individual or group. All approaches to the interpretation of way of living and lifestyles are grouped into three groups: a synonymous approach in which the terms «way of living» and «lifestyle» are regarded as interchangeable; an approach in which lifestyle is viewed as a narrower concept than way of living; an approach where these concepts are differentiated and treated as equivalent. On the basis of various definitions of these concepts, their comparison was made and a conclusion about the substantive sub-catherogality of the concept of «lifestyle» with respect to the concept of «way of living» was made. Possibilities of using these categories to analyze the phenomenon of individual health are considered. The necessity of the multidisciplinary nature of using of the concepts of «way of living» and «lifestyle» in its research is shown. Based on its features, it is concluded that the using of the concept of «healthy way of living» over the concept of «healthy lifestyle». The second is considered as an individualized version of the first. It is shown that the use of one of the studied concepts does not limit the possibility of using another. Their differentiation can be made depending on the concept of the research taking into account the continuums: «norm – variability», «social – individual».
The Potential of Using the Concepts «Way of Living» and «Life Style» for Sociological Analysis of Individual Health Practices
Keywords: спосіб життя; стиль життя; здоровий спосіб життя; соціальні практики; індивідуальне здоров’я; way of living; lifestyle; healthy way of living; social practices; individual health; 316.013